The The Correlation between Motivation and Anesthetists’ Working Performance in Banyumas Regency: English - Achmad Fadilah, Rizal; Sukmaningtyas, Wilis; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2023)
Background: The performance of health workers is a very crucial issue to be studied in order to maintain and improve health services. The impact that occurs if the performance of health workers in the hospital is not good can cause patients and families to feel dissatisfied, patients and families will not use health services again. One of the factors that affect performance is motivation. Objective: Knowing the relationship between motivation and the performance of anesthesiologists in the Banyumas Regency area. Research: The research method is correlation analytics research with a cross sectional approach. The sampling technique used total sampling, a total of thirty-nine respondents. Data collection using work motivation and performance questionnaires. Bivariate analysis using spearman-rank. Results: The results of the study obtained a percentage of 39 respondents of anesthesiologists in the Banyumas Regency area with sufficient motivation as many as 28 respondents (71.79%) and respondents who had sufficient performance as many as 31 respondents (79.98%). The results of spearman-rank analysis showed a significant relationship, work motivation with the performance of anesthesiologists with a correlation value of 0.733 and a 2-tailed sig of 0.000. Conclusion: Advice for the anesthesiologist profession who is especially incorporated in the organization at the DPC IPAI Banyumas Branch Secretariat which researchers recommend is expected to improve the quality and quantity of health services to patients and families, namely by carrying out predetermined procedures and friendly, so that patients and families feel comfortable and served with satisfaction for the services provided.